Covert marketing in Social commerce: Muslim Consumers' Perception of Viral Products in the Perspective of Islamic Business Ethics - Mohammad Saiful Rifai; Fatkhur Rohman Albanjari; Mukhamad Rinda Rifa’i; Fadilla Muhammad Mahdi; Ilza Febrina (Jurnal Iqtisad, 2026)
This study is motivated by the rapid development of increasingly creative digital marketing strategies that may raise ethical concerns when conducted without transparency. This study aims to analyze Muslim consumer perceptions of covert marketing practices on viral products in TikTok Shop from the perspective of Islamic business ethics. This research employed a qualitative method with a descriptive approach. Data were collected through in-depth interviews with business actors and consumers. The researcher also conducted observations and documentation related to covert marketing practices. Data analysis techniques included data reduction, data presentation, and conclusion drawing. The findings indicate that covert marketing practices are considered effective in attracting consumer attention because they are able to build emotional closeness and increase trust through promotions presented naturally. Such strategies are commonly implemented through social media, personal recommendations, and the use of third parties in delivering promotional messages. However, in practice, several forms of marketing were found to potentially create unclear information and manipulate consumer perceptions. From the perspective of Islamic business ethics, marketing activities should be based on the principles of honesty, transparency, responsibility, and fairness. Therefore, covert marketing may be permissible as long as it does not involve deception, gharar (uncertainty), or misleading information for consumers. This study emphasizes that the balance between marketing creativity and the implementation of Islamic business ethics is an important factor in creating healthy and sustainable business practices.